The Impact of Marketing Communications on Consumer Behavior - Manasra, Mahmoud (European Scientific Journal, ESJ, 2025)
Marketing is a crucial function in organizations that aim to retain existing customers and attract new ones to achieve long-term, sustainable profitability. The current technological developments in communication media have made it easy for the marketing communication function to perform at its full capacity. The primary objective of marketing communication is to create consumer awareness about the products and services offered. Hence, sometimes organizations may rely solely on digital channels to raise product and service awareness and build brands. On the other hand, they may concentrate on different marketing channels, using cross-marketing, including traditional channels like TV and radio and parallel digital channels. Depending on the situation, companies use multiple communication channels to influence consumers’ buying decisions and their behavior toward brands. The Saudi telecom players have been deliberately investing in marketing activities to influence consumers across genders, nationalities, groups, and ages. They have been investing in traditional communication channels during the last decade. Their messages were distributed among all traditional channels, especially TV, outdoor, and Radio. Understanding of varying consumer behavioral patterns, such as motivation, knowledge, and information processing, will aid in designing, building, and implementing effective marketing communication strategies.